Editorial: simplifying screening for primary liver cancer – do the LCR1 and LCR2 tests hold the key?. Issue 5 (11th February 2019) - Drake, Thomas M.; Bird, Thomas G.
Abstract : Linked Content This article is linked to Poynard et al papers. To view these articles, visit https://doi.org/10.1111/apt.15082 and https://doi.org/10.1111/apt.15135 .